Constructing and Analyzing a Smart Cleaning Machine with IoT Capabilities for Home Upkeep - Anderson, Michael; Li, Xue (Journal of Computer Science and Software Applications, 2024)
With advancements in science and technology and the increasing demand for a higher quality of life, an Internet of Things (IoT)-based intelligent cleaning machine has been proposed. The design and structure of this cleaning machine are elaborated upon, along with an analysis of its operating principles. This intelligent cleaning machine offers a solution to the labor-intensive and time-consuming nature of manual cleaning, particularly in hard-to-reach areas such as under beds and sofas. Enhancements to the traditional intelligent cleaning machines have been made to enable remote monitoring via mobile devices, thereby improving cleaning efficiency and quality to align with the fast pace of modern life.